Appendiceal intussusception, a peroperative surprise: A case report - Arslan, Baha; Yılmaz, Tuğbahan; Erol, Varlık; Gülay, Hüseyin (Journal of Surgery and Medicine, 2019)
Intussusception of the appendix is very uncommon and when encountered, it may alter surgical procedures. For this reason, it should be kept in mind that appendiceal intussusception may occur in every patient diagnosed with acute appendicitis. It is critical to consider appendiceal intussusception in patients presenting with recurrent nausea, vomiting and chronic abdominal pain.